Debt, Taxes and Leasing A Note - BREALEY, R. A.; YOUNG, C. M. (Journal of Finance, 1980)
This paper discusses the implications of Miller's paper “Debt and Taxes” for the valuation of leases. It shows that if Miller's equilibrium holds, leasing is only likely to dominate debt and equity for companies in temporary nontaxpaying positions.